Proximal versus distal femoral derotation osteotomy in bilateral cerebral palsy. (7th May 2018) - Niklasch, Mirjam; Boyer, Elizabeth R; Novacheck, Tom; Dreher, Thomas; Schwartz, Michael
Abstract : Aim: Femoral derotation osteotomy (FDO) can be conducted either proximally or distally to correct internal rotation gait (IRG) and increased anteversion in children with cerebral palsy (CP). Previous studies with limited numbers of participants have presented comparable short‐term static and kinematic outcomes for both techniques. The objective of this retrospective multicentre study was to verify this thesis with a larger number of patients. Method: In total, 119 children with CP and IRG were included after matching the groups on preoperative mean stance hip rotation: 67 intertrochanteric (proximal group) FDO (average age at surgery 9y [SD 3y]); 52 supracondylar (distal group) FDO (average age at surgery 12y [SD 3y]). One random limb of each child was analyzed. Both transverse plane kinematic gait data and torsional parameters of clinical examination were assessed preoperatively and postoperatively. Results: On average, both groups' mean hip rotation and midpoint of hip rotation improved postoperatively, and groups did not differ preoperatively or postoperatively for these variables ( p >0.05). Interpretation: The osteotomy location does not influence short‐term gait kinematics nor static measurements. Therefore, the choice of performing proximal or distal FDO in children with CP for treatment of IRG and increased anteversion should be motivated by considerations other than these outcome parameters. What this paper adds: Femoral derotation osteotomy (FDO) location does not influence mean stance hip rotation in cerebral palsy (CP). FDO location does not influence mid‐point hip rotation in CP. FDO location should be motivated by concomitant procedures performed. What this paper adds: Femoral derotation osteotomy (FDO) location does not influence mean stance hip rotation in cerebral palsy (CP). FDO location does not influence mid‐point hip rotation in CP. FDO location should be motivated by concomitant procedures performed. This article is commented on by de Morais Filho on pages971–972 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.